2018
DOI: 10.1007/s00415-018-9081-7
|View full text |Cite
|
Sign up to set email alerts
|

Functioning and quality of life in patients with neuropathy associated with anti-MAG antibodies

Abstract: Although anti-myelin-associated glycoprotein (MAG) antibody neuropathy is reported as a slowly progressive disease, it can lead to significant disability and impairment of health-related quality of life (HR-QoL) and social participation. The aim of this cross-sectional study was to evaluate the functioning and HR-QoL determinants in 67 patients with anti-MAG neuropathy in terms of the International Classification of Functioning, Disability, and Health (ICF). Evaluations included: Medical Research Council (MRC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…6 To date, several scales and measures have been suggested as general functionality parameters in anti-MAG antibody neuropathy, such as the ability to walk 7 or quantitative gait analysis, 8 Recently, a correlation between the objective evaluation of muscular strength with the vigorimeter and the patient's reported scale Inflammatory-RODS (I-RODS) has been observed in immunemediated neuropathies including anti-MAG antibody neuropathies. 9 These findings have been confirmed by another recent study, 10 In a recently published multicenter cross-sectional study 12 we evaluated the functioning and HRQoL determinants in 67 patients with anti-MAG antibody neuropathy in compliance of the terms defined by the ICF. In our cohort we observed that walking ability and fatigue were the most reliable predictors of physical and mental aspects of QoL, respectively.…”
Section: Introductionsupporting
confidence: 60%
See 1 more Smart Citation
“…6 To date, several scales and measures have been suggested as general functionality parameters in anti-MAG antibody neuropathy, such as the ability to walk 7 or quantitative gait analysis, 8 Recently, a correlation between the objective evaluation of muscular strength with the vigorimeter and the patient's reported scale Inflammatory-RODS (I-RODS) has been observed in immunemediated neuropathies including anti-MAG antibody neuropathies. 9 These findings have been confirmed by another recent study, 10 In a recently published multicenter cross-sectional study 12 we evaluated the functioning and HRQoL determinants in 67 patients with anti-MAG antibody neuropathy in compliance of the terms defined by the ICF. In our cohort we observed that walking ability and fatigue were the most reliable predictors of physical and mental aspects of QoL, respectively.…”
Section: Introductionsupporting
confidence: 60%
“…In a recently published multicenter cross‐sectional study we evaluated the functioning and HRQoL determinants in 67 patients with anti‐MAG antibody neuropathy in compliance of the terms defined by the ICF. In our cohort we observed that walking ability and fatigue were the most reliable predictors of physical and mental aspects of QoL, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…For the examination of balance performances in PNP, the Berg Balance Scale (BBS) was the most used clinical scale [ 73 , 93 , 94 , 95 , 96 , 97 , 98 , 99 ]. BBS is a standard clinical measure to assess static balance impairments and a robust method to study postural control [ 100 ].…”
Section: Discussionmentioning
confidence: 99%
“…MAG neuropathy can present with mild clinical deficit, and remain stable or only slowly progressive for many years, but can then enter a more rapidly progressive course that can lead to disability, probably resulting from cumulative nerve damage [14,15 ▪ ,16]. There is no correlation between antibody titers and severity of the neuropathy, although increasing antibody titers are probably indicative of expansion of the monoclonal gammopathy.…”
Section: Correlation Of Antibody Titers With Disease Severity or Prog...mentioning
confidence: 99%
“…An increasing number of laboratories use the Buhlmann MAG ELISA kits, in which sera are tested at a single dilution of 1:1000, and the binding quantified by comparison to a standard titration curve generated with serial dilutions of pooled reactive sera [16]. This system allows for quantitative comparisons of antibody binding between different patients, or between serial samples of the same patient.…”
Section: Interpreting Anti-myelin-associated Glycoprotein Antibody As...mentioning
confidence: 99%